Evidence of groundwater vulnerability to climate variability and economic growth in coastal Kenya - Ferrer Ramos, N; Folch, A; Fernàndez-Garcia, D; Lane, M; Thomas, M; Gathenya, JM; Wara, C; Thomson, P; Custodio, E; Hope, R (Elsevier, 2020)
Climate change and future abstraction regimes will influence the availability of groundwater resources. To alleviate any potential negative effects on aquifer systems and dependent industrial and human uses, it is important to develop long-term water management plans. This study evaluates the effect of climate change and future increased groundwater demand from a coastal aquifer located in Kwale County in southern Kenya. A previously calibrated numerical groundwater flow model has been used as an assessment tool to study how future climate (precipitation and temperature variation) and groundwater abstraction changes will affect the aquifer system. The groundwater flow model was built to simulate the period 2010 to 2017, and eight future model scenarios were developed that cover six hypothetical future years. Future groundwater abstraction has been based on current allocations and future estimates made by Kenya’s Water Resources Authority. Future rainfall scenarios have been constructed based on a long historical data series (from 1959 to 2017) and the Standard Precipitation Index. The main results show that future abstraction increases due to economic growth exerts a minimum impact compared with expected climate variability. Recharge depends on intense rain events with important implications for both dry periods and for an average rainfall year. A succession of extended dry seasons may affect all water users. However, the groundwater level decline in the local shallow aquifer can reach five meters, with important consequences for local community water supplies. The most significant groundwater decline in drought periods is observed in the area surrounding the pumping wellfields in the deep aquifers, where the effects of drought and significant abstraction are multiplied. However, the effect of increased abstraction on the shallow aquifer system is limited. Despite groundwater level decline observed during prolonged dry periods, a dry period followed by a humid period leads to the relatively swift recovery of the groundwater system.